The Opportunistic Pathogen Propionibacterium acnes: Insights into Typing, Human Disease, Clonal Diversification and CAMP Factor Evolution - McDowell, Andrew; Nagy, István; Magyari, Márta; Barnard, Emma; Patrick, Sheila (PLOS ONE, 2013)
We previously described a Multilocus Sequence Typing (MLST) scheme based on eight genes that facilitates population genetic and evolutionary analysis of P. acnes. While MLST is a portable method for unambiguous typing of bacteria, it is expensive and labour intensive. Against this background, we now describe a refined version of this scheme based on two housekeeping (aroE; guaA) and two putative virulence (tly; camp2) genes (MLST4) that correctly predicted the phylogroup (IA1, IA2, IB, IC, II, III), clonal complex (CC) and sequence type (ST) (novel or described) status for 91% isolates (n = 372) via cross-referencing of the four gene allelic profiles to the full eight gene versions available in the MLST database (http://pubmlst.org/pacnes/). Even in the small number of cases where specific STs were not completely resolved, the MLST4 method still correctly determined phylogroup and CC membership. Examination of nucleotide changes within all the MLST loci provides evidence that point mutations generate new alleles approximately 1.5 times as frequently as recombination; although the latter still plays an important role in the bacterium's evolution. The secreted/cell-associated ‘virulence’ factors tly and camp2 show no clear evidence of episodic or pervasive positive selection and have diversified at a rate similar to housekeeping loci. The co-evolution of these genes with the core genome might also indicate a role in commensal/normal existence constraining their diversity and preventing their loss from the P. acnes population. The possibility that members of the expanded CAMP factor protein family, including camp2, may have been lost from other propionibacteria, but not P. acnes, would further argue for a possible role in niche/host adaption leading to their retention within the genome. These evolutionary insights may prove important for discussions surrounding camp2 as an immunotherapy target for acne, and the effect such treatments may have on commensal lineages.